Character Education Based on Pancasila Values Through Curriculum 2013 on Primary Education Children in Madura - Dian Eka Indriani (JPDI (Jurnal Pendidikan Dasar Indonesia), 2017)
The importance of character education seems to have been recognized by the government. As an expression comes from the founding father of the nation that the battle will be more severe because the opponent is no longer come from the outside but from the inside, then through character education is proclaimed in the curriculum, especially in curriculum 2013, an obvious emphasis on the spiritual and social through their first core competencies and second core competencies that must exist in all subjects in school. This study is a qualitative descriptive study with triangulation, using data collection techniques, namely questionnaire, observation and interview. Research will be conducted in an elementary school using Curriculum 2013 in the District Kamal, there are five primary schools in Kamal those are SDN Banyuajuh 2, SDN Banyuajuh 3, SDN Banyuajuh 6, SDN Kamal 1, SDN Gili Anyar. The results of this study are expected to examine more deeper in the development of character-building nation, ie characters that contain values of Pancasila as education that contains the values of Pancasila with the essence of Pancasila as the outlook of the nation is a prime shield for the challenges and threats as forming the national character that is unique and distinctive that became distinguishing element between one nation by another nation.